A Correlated‐K Parameterization for O 2 Photolysis in the Schumann‐Runge Bands - Ji, Aoshuang (2024)
A recent study comparing ozone column depths and methane lifetimes at varied atmospheric O2 (pO2) levels calculated in the Kasting-group 1-D photochemical model and the Whole Atmosphere Community Climate Model version 6 (WACCM6) 3-D model (Ji, Kasting, et al., 2023; https://doi.org/10.1098/rsos.230056) has exposed weaknesses in both models in parameterizing photolysis in the O2 Schumann-Runge bands, 175–205 nm. WACCM6 does a good job for Earth´s present atmosphere but neglects scattering, which becomes important at low pO2. The 1-D model includes scattering but is based on an out-of-date band model, and it neglects the temperature dependence of photolysis at low pO2. We have revised and improved the 1-D photochemical model by replacing the old O2 photolysis algorithm with a new correlated-k parameterization, which improves accuracy for all O2 levels and all temperature profiles. The WACCM6 parameterization was also included in the 1-D model for comparative purposes. The correlated-k and WACCM6 photolysis algorithms agree well for both the present atmosphere and for an atmosphere containing 10−3 times the present O2 level, but only if multiple scattering is included at low pO2. The correlated-k parameterization will be made available to photochemical modeling groups who might choose to adopt it.